The Role Of Knowledge Management Processes In Improving Organizational Performance - البهلول , علي (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The research sought to examine the relationship between knowledge management processes on the one hand, and between organizational performance in Tishreen University on the other hand, where the researcher distributed a questionnaire to a simple random sample of the employees in the University of Tishreen reached (250) questionnaire, since(228) responses were received, and(158) questionnaire were used for analysis. To test the relationship, the researcher used the Student T test for one sample, as well as the Pearson correlation coefficient. The research concluded that there is a decrease in the level each of sharing and storage knowledge among employees in colleges under study, as well as a decrease in the level each of efficiency and effectiveness in the colleges under study. The research concluded that there is a significant relationship between knowledge management processes and organizational performance at Tishreen University, and thus the existence of the role of knowledge management processes in improving level organizational performance. The research presented a set of recommendations and proposals related to improving mechanisms for sharing and storing knowledge, as well as using optimally available resources.